#### Answer

Correct

#### Work Step by Step

$12y-(3y-1)=12y-3y+1\rightarrow$ apply distributive property
$12y-3y+1=12y-3y+1$

Published by
Pearson

ISBN 10:
0321955048

ISBN 13:
978-0-32195-504-3

Correct

$12y-(3y-1)=12y-3y+1\rightarrow$ apply distributive property
$12y-3y+1=12y-3y+1$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.